Juvenile Myoclonic Epilepsy Shows Potential Structural White Matter Abnormalities: A TBSS Study - Domin, Martin; Bartels, Sabine; Geithner, Julia; Wang, Zhong I.; Runge, Uwe; Grothe, Matthias; Langner, Soenke; von Podewils, Felix (Frontiers in Neurology, 2018)
Background: Several studies on patients with juvenile myoclonic epilepsy (JME) showed widespread white matter (WM) abnormalities in the brain. The aim of this study was to investigate potential structural abnormalities in JME patients (1) compared to healthy controls, (2) among JME subgroups with or without photoparoxysmal responses (PPR), and (3) in correlation with clinical variables. Methods: A selection of 31 patients with JME (12 PPR positive) and 27 age and gender matched healthy controls (HC) were studied at a tertiary epilepsy centre. Fractional anisotropy (FA) was calculated and intergroup differences analysed using Tract Based Spatial Statistics (TBSS). Results: Compared to HC the JME group showed reduced FA widespread and bilateral in the longitudinal fasciculus, inferior fronto-occipital fasciculus, corticospinal tract, anterior and posterior thalamic radiation, corona radiata, corpus callosum, cingulate gyrus and external capsule (p<0.01). Subgroup analysis revealed no significant differences of WM alterations between PPR positive and negative patients and with clinical and epilepsy-related factors. Conclusions: Widespread microstructural abnormalities among patients with JME have been identified. Prior findings of frontal and thalamofrontal microstructural abnormalities have been confirmed. Additionally, microstructural abnormalities were found in widespread extra-frontal regions that may help to validate pathophysiological concepts of JME.